Bictegravir combined with emtricitabine and tenofovir alafenamide versus dolutegravir, abacavir, and lamivudine for initial treatment of HIV-1 infection: week 96 results from a randomised, double-blind, multicentre, phase 3, non-inferiority trial. Issue 6 (June 2019) - Wohl, David A; Yazdanpanah, Yazdan; Baumgarten, Axel; Clarke, Amanda; Thompson, Melanie A; Brinson, Cynthia; Hagins, Debbie; Ramgopal, Moti N; Antinori, Andrea; Wei, Xuelian; Acosta, Rima; Collins, Sean E; et al.
Summary: Background: Bictegravir co-formulated with emtricitabine and tenofovir alafenamide as a fixed-dose combination is recommended for treatment of HIV-1-infection and might be better tolerated than other integrase inhibitor-based single-tablet regimens, but long-term outcomes data are not available. We assessed the efficacy, safety and tolerability of bictegravir, emtricitabine, and tenofovir alafenamide compared with co-formulated dolutegravir, abacavir, and lamivudine at week 96. Methods: This ongoing, randomised, double-blind, multicentre, active-controlled, phase 3, non-inferiority trial was done at 122 outpatient centres in nine countries. We enrolled adults (aged ≥18 years) living with HIV who were treatment naive and HLA-B*5701 negative, did not have hepatitis B virus infection, and had an estimated glomerular filtration rate of at least 50 mL/min. We randomly assigned participants (1:1) to receive co-formulated bictegravir 50 mg, emtricitabine 200 mg, and tenofovir alafenamide 25 mg (the bictegravir group) or co-formulated dolutegravir 50 mg, abacavir 600 mg, and lamivudine 300 mg (the dolutegravir group), each with matching placebo, once daily for 144 weeks. Treatment allocation was masked to all participants and investigators. All participants who received at least one dose of study drug were included in primary efficacy and safety analyses. We previously reported the primary endpoint. Here, we report the week 96 secondary outcome of proportion of participants with plasma HIV-1 RNA less than 50 copies per mL at week 96 by US Food and Drug Administration snapshot algorithm, with a prespecified non-inferiority margin of −12%. This study was registered withClinicalTrials.gov, numberNCT02607930 . Findings: Between Nov 13, 2015, and July 14, 2016, we screened 739 participants, of whom 108 were excluded and 631 enrolled and randomly assigned to bictegravir, emtricitabine, and tenofovir alafenamide (n=316) or dolutegravir, abacavir, and lamivudine (n=315). Two participants in the bictegravir group did not receive at least one dose of their assigned drug and were excluded from analyses. At week 96, bictegravir, emtricitabine, and tenofovir alafenamide was non-inferior to dolutegravir, abacavir, and lamivudine, with 276 (88%) of 314 participants in the bictegravir group versus 283 (90%) of 315 participants in the dolutegravir group achieving HIV-1 RNA less than 50 copies per mL (difference −1·9%; 95% CI −6·9 to 3·1). The most common adverse events were nausea (36 [11%] of 314 for the bictegravir group vs 76 [24%] of 315 for the dolutegravir group), diarrhoea (48 [15%] vs 50 [16%]), and headache (41 [13%] vs 51 [16%]). 36 (11%) participants in the bictegravir group versus 39 (12%) participants in the dolutegravir group had a serious adverse event. Two individuals died in the bictegravir group (recreational drug overdose and suicide, neither of which was treatment related) and none died in the dolutegravir group. No participants discontinued because of adverse events in the bictegravir group compared with five (2%) of 315 in the dolutegravir group. Study drug-related adverse events were reported for 89 (28%) participants in the bictegravir group and 127 (40%) in the dolutegravir group. Interpretation: These week 96 data support bictegravir, emtricitabine, and tenofovir alafenamide as a safe, well tolerated, and durable treatment for people living with HIV-1 with no emergent resistance. Funding: Gilead Sciences, Inc.